Strategi Pemasaran Berbasis Website, Bazar, dan Pelatihan Kerajinan Rajut untuk Pengembangan Tenun Leny Bumpak - Putri, Natasya; Rahmahnusiya, Elvina Triya; Alfajri, Ockto; Zaki, Khozin; Indra, Yetti Afrida (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including in empowering rural communities. Leny Bumpak Tenun, as one of the MSMEs, has challenges in expanding its market reach due to limited digital marketing strategies and product innovation. This community service activity aims to support the development of Leny Bumpak Tenun through marketing strategies, namely creating a website as a digital promotional media, implementing a bazaar to introduce and sell products directly, and knitting craft training to increase product variety and empower local communities. The implementation method includes creating a website that displays a product catalog and ordering system, technical training in website management, and knitting training that produces creative products such as key chains and accessories. The results of the activity showed an increase in brand awareness, community skills, and wider market potential, making this approach effective in supporting the sustainability of locally-based MSMEs.